The Role Of Work Satisfaction Mediation In Company System Digitalization In Influencing Employee Performance - mardiman -; Surya Aprilia Hasibuan; Edi Suryadi; Ade Sobandi (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Businesses can boost staff achievement and promote profitable endeavors by digitizing their operations. Like the benefit of job satisfaction, the value of system digitization can lead to significant developing organizations outcomes that are economically viable and enhance worker efficiency as well as performance. The research methodology included both quantitative analysis and the validation methods. Using a sample of 91 participants, a method called Slovin was used to conduct the sampling method. Every piece of data was gathered through the dissemination of surveys. The PLS technique was applied in SEM analysis, particularly with small boxes, to evaluate the assumptions. The conclusions are made The findings demonstrate that staff efficiency and work enjoyment are positively impacted by the digitization of business processes. Furthermore, job happiness and total productivity of workers are positively impacted by the digitization of corporate systems, and job satisfaction might function as a buffer throughout the two developments.